Multifunctional PN optoelectronic synapse and its smart integration towards augmented artificial visual system - Qinghong Lin; Yangbin Zhu; Xin Hu; Jiayu Sun; Zhen Wang; Kejia You; Xuan Guo; Yue Wang; Deli Li; Liangxu Lin; Yi Zhao; Guangyu Wang; et al. (npj Flexible Electronics)
Abstract Mimicking and extending biological sensory memory processing functions and systems—that play significant roles in enhancing interconnections of the human-physical world—are highly preferable for the Internet of Things. However, conventional artificial sensory systems usually consisted of separated modules or relied on perception-memory-processing devices with applications in a limited domain. Here, we propose a self-rectifying multifunctional synapse based on a unique PN optoelectrical memristor interface, achieving an augmented artificial visual system and multifunctional interconnected ports. The synapse realizes in-sensor motion perception and non-contact control beyond perception-memory-processing functions. The self-rectifying device can self-suppress the sneak current in cross-arrays, enabling large-scale and high-density integration. Further integrating synapse with quantum dot light-emitting diodes (QLEDs) evolves more powerful functions like hardware noise filtering and perception-memory-processing-displaying smart systems.